2020
DOI: 10.1101/2020.04.29.069005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suicidal Thoughts, Behaviors, and Event-Related Potentials: A Systematic Review and Meta-Analysis

Abstract: Suicidal thoughts and behaviors (STBs) are thought to be the result, at least in part, of abnormalities in various neural systems. Event-related potentials (ERPs) are a useful method for studying neural activity, and can be leveraged to study neural deficits related to STBs, but it is unknown how effective ERPs are at differentiating various STB groups. The present metaanalysis examined how well ERPs can differentiate those with and without suicidal ideation (SI), suicide attempts (SA), and those determined to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 134 publications
(135 reference statements)
1
4
0
Order By: Relevance
“…Finally, this study did not find other significant whole-brain connectivity betweengroup differences. Results are consistent with a recent meta-analyses of event-related potential studies, which found small or no effects in larger studies comparing those with suicide attempt to suicidal ideation alone 51 . Null findings across methodologies using stringent control groups may reflect the need for more nuanced investigation and interpretation of the interplay between biopsychosocial factors to differentiate those with lifetime history of suicide attempt(s) from SDVT alone 5 .…”
Section: Discussionsupporting
confidence: 91%
“…Finally, this study did not find other significant whole-brain connectivity betweengroup differences. Results are consistent with a recent meta-analyses of event-related potential studies, which found small or no effects in larger studies comparing those with suicide attempt to suicidal ideation alone 51 . Null findings across methodologies using stringent control groups may reflect the need for more nuanced investigation and interpretation of the interplay between biopsychosocial factors to differentiate those with lifetime history of suicide attempt(s) from SDVT alone 5 .…”
Section: Discussionsupporting
confidence: 91%
“…The current mixture of measures being used hampers development of the field. Measurement issues with single-item assessments of suicide attempts [ 157 ] or contributors of suicide capability [ 66 ] are recurring issues. As Kramer et al [ 158 ] previously argued with regards to acquired capability measures, future research will benefit from using psychometrically sound measures rather than partial versions to allow accurate interpretations and conclusions to be drawn across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only considering our study and the study by Tsypes and colleagues, it is difficult to decide between these two scenarios. We recently conducted a meta-analysis on the relationship between ERPs and suicidal ideation and found a very small (viz., Hedges’ g = −.06) blunting of the RewP in individuals experiencing suicidal ideation compared to controls (Gallyer et al, 2021). For reasons we discuss in that meta-analytic review, including the small effect size and the high correlation between depression and suicidal ideation (Rogers et al, 2016), it cannot be ruled out that this blunting of the RewP is a false positive.…”
Section: Discussionmentioning
confidence: 99%
“…We chose two effect size ranges, resulting in two separate equivalence tests: (1) lower bound d = −0.24 and upper bound d = 0.24 and (2) lower bound d = −0.60 and upper bound d = 0.60. Our first effect size estimate was based on recent meta-analytic evidence that the upper bound on the relationship between ERPs and suicidal ideation is Hedges’ g = 0.24, and the second effect size range was based on the effect reported in the study we sought to conceptually replicate (Gallyer et al, 2021; Tsypes et al, 2019). For our equivalence tests, we used the PCAΔRewP as our dependent variable and ideation group (no SI, recent SI) as the independent variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation